Investigation of Fish Resource in the Yongding River System - ZHOU Xushen; HU Zhen; CUI Wenyan; XU Ning; WANG Liming (Renmin Zhujiang)
To understand the population makeup and fauna distribution of fish stocks at YongdingRiver. Based on fish surveys in 2016 and relevant literature, this paper summarizes the species offish in Yongding River, concludes that Yongding River is belong to riverplain region afteranalysis,and obtains the loss index of fish according to existing species and historical data. Theresults show that there are 44 species of fish in Yongding River system, which are dominated bymiddle and low-layer, omnivorous, small fishes. The proportion of Cyprinidae is 50%, with thelargest number of species, and the other species are fewer. There are 31 species appeared inexisting species and historical data, but 13 existing species do not appear in the historical data.The historical investigation might be incomprehensive,so the 13 species should be included in thehistorical data. The bio-loss index of fish is 0.667 and the marks of fish index is 48.93, whichindicate that fishes are in the sub-health level. The ecological protection of the Yongding Rivershould be strengthened to restore the fish habitat.